2011
DOI: 10.1053/j.gastro.2010.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Light-Scattering Technologies for Field Carcinogenesis Detection: A Modality for Endoscopic Prescreening

Abstract: Colonoscopy has revolutionized colorectal cancer (CRC) screening resulting in a decrease in both CRC mortality and incidence. Despite this, CRC still ranks as the second leading cause of cancer deaths among Americans underscoring the need to both increase availability and accuracy of colonoscopy. The latter considerations provide the impetus for much of the current research into adjunctive imaging technologies. Recent advances in improving detection of dysplasia that have translated into clinical practice incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 51 publications
1
47
0
1
Order By: Relevance
“…Mechanistically, this provides a general road map of which morphological structures to investigate. Ongoing research to implicate specific mucosal components suggests that the alterations occur due to a combination of intracellular (e.g., condensation of chromatin in the nucleus [2][3][4] or abnormalities in the cytoskeleton 5 ) and extracelluar components (e.g., collagen cross-linking 4,6 ). Interestingly, these changes appear to be attenuated versions of other classical markers of neoplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, this provides a general road map of which morphological structures to investigate. Ongoing research to implicate specific mucosal components suggests that the alterations occur due to a combination of intracellular (e.g., condensation of chromatin in the nucleus [2][3][4] or abnormalities in the cytoskeleton 5 ) and extracelluar components (e.g., collagen cross-linking 4,6 ). Interestingly, these changes appear to be attenuated versions of other classical markers of neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Several changes whose role in field carcinogenesis has been implicated include chromatin condensation, [2][3][4] cytoskeleton disruption, 5 and collagen crosslinking in the extracellular matrix. 6 Still, the exact origin and carcinogenic advantage these transformations confer are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…5 With respect to the colon, this suggests that normal-appearing mucosa within the colon could be assessed for molecular alterations as a way to gauge the risk of harboring concurrent colon adenomas or cancer or developing metachronous adenomas or cancer. 6 In fact, previous studies evaluating the morphologically-normal colon mucosa (MNCM) have demonstrated an association between DNA methylation of certain cancer-related genes and neoplastic lesions located elsewhere in the colon. 2,3,[7][8][9][10][11] A direct correlation between the aberrant methylation of APC, DKK1, CDKN2A/p16, and SFRP4 in the apparently normal colon mucosa and the presence of adjacent colon cancer has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Backman and Roy have proposed measurement of the field effect of colon carcinogenesis using light scattering techniques as a means of risk stratification and prescreening for CRC. 11 Additionally, optical coherence tomography (OCT), a depth-resolved optical imaging technique, has been used to image the microstructure of intestinal epithelium during endoscopy to evaluate tissue health. [12][13][14] Angle-resolved low coherence interferometry (a/LCI) is a light scattering technique that combines the abilities of light scattering spectroscopy to detect morphological changes in cell nuclei with the depth-resolving power of OCT.…”
Section: Introductionmentioning
confidence: 99%